PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF DIGITAL BANGUN DATAR MENGGUNAKAN POLA PERMAINAN TRADISIONAL ENGKLEK DENGAN MODEL ADDIE PADA PELAJARAAN MATEMATIKA KELAS IV - Risa Amalia Febrianti, - (2022)
The aim of this study is that to develop an interactive digital learning media based on the traditional engklek game in the material of flat shapes for fourth grade students at SDN Leuwiranji 03 in order to increase students' interest in learning in the flat shape material. This study was conducted since based on the results of interviews with fourth grade teachers at SDN Leuwiranji 03, there are still many students who do not understand the characteristics of flat shapes to the concept of how to find the perimeter and area of flat shapes. In the learning process, the learning media used are only in the form of textbooks and objects which are around the classroom or school so that it makes students less focused and interested in listening to the teacher's explanation. The subjects in this study were fourth grade students who conducted learning process using interactive digital learning media based on the traditional engklek game. Moreover, this study used qualitative research with ethnography and qualitative descriptive methods. Qualitative ethnographic methods were used to collect data and information about the traditional engklek game. In addition, researchers used the adaptation of the ADDIE model in the development of interactive digital learning media during its integration with traditional engklek game. The ADDIE model has 5 steps that are analysis, design, development, implementation and evaluation. Data collection techniques used participant observation methods, in-depth interviews and document analysis. In the development step of learning media, researchers used the Macromedia Flash CS6 application to be able to create the desired media products and use teaching materials in the form of textbooks in delivering material. The textbook is a source of material which will be used in interactive digital learning media. The data analysis technique which had conducted had five steps that were identifying data, classifying data, describing data, interpreting data and concluding data. The results of this study are in the form of a learning implementation plan (RPP) document and learning media products which can increase student interest in learning and motivation. Key words: Learning Media, Engklek Game, ADDIE Model